2018
DOI: 10.1111/jdv.14973
|View full text |Cite
|
Sign up to set email alerts
|

Both children and adult patients with difficult‐to‐treat atopic dermatitis have high prevalences of concomitant allergic contact dermatitis and are frequently polysensitized

Abstract: BackgroundConcomitant allergic contact dermatitis (ACD) has been described as a possible cause of atopic dermatitis (AD) becoming difficult‐to‐treat. However, contact sensitization in this patient group has barely been studied.ObjectiveTo study the occurrence of ACD in a population of difficult‐to‐treat AD children and adults.MethodsClinical and patch test information of 48 patients with difficult‐to‐treat AD unresponsive to conventional outpatient treatments was gathered retrospectively. We studied prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 52 publications
1
28
0
2
Order By: Relevance
“…28 Penetration of MI can be enhanced by changes in the skin barrier or by the presence of atopic inflammatory lesions. 29 In our series, relapses occurred more frequently when the initial localization of the dermatitis was on the hands. The hands are more often exposed to different types of product that are likely to contain MI, including unlabelled industrial applications.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…28 Penetration of MI can be enhanced by changes in the skin barrier or by the presence of atopic inflammatory lesions. 29 In our series, relapses occurred more frequently when the initial localization of the dermatitis was on the hands. The hands are more often exposed to different types of product that are likely to contain MI, including unlabelled industrial applications.…”
Section: Resultsmentioning
confidence: 47%
“…Cvetkovski et al showed that atopy and atopic dermatitis are risk factors for poor prognosis in the evolution of hand eczema . Penetration of MI can be enhanced by changes in the skin barrier or by the presence of atopic inflammatory lesions . In our series, relapses occurred more frequently when the initial localization of the dermatitis was on the hands.…”
Section: Discussionmentioning
confidence: 43%
“…This can create diagnostic challenges in clinical practice as well as in epidemiological studies. A recent study of dermatology patients with difficult‐to‐treat AD showed a high prevalence of contact allergy among both children and adults …”
Section: Discussionmentioning
confidence: 99%
“…A case of mild angular cheilitis, which could have been mistaken as a "minimal sign" of atopic eczema, was actually due to using a toothpaste with stannuous fluoride; positive patch test reactions were seen to the toothpaste as well as tin 50% pet., which is otherwise an extremely rare allergen [210]. Both children and adult patients with difficult-to-treat atopic dermatitis have high prevalences of concomitant allergic contact dermatitis and are frequently polysensitized [211], hence patch testing to identify contact allergy and secondary ACD to active ingredients or excipients is very important.…”
Section: Medicines (Active Principles and Excipients) And Cosmeticsmentioning
confidence: 99%